Slankekurens historie: Ernæringsdiskurser og slanketendenser siden 1950’erne - Andersen, Julie Stæhr (Forum for Idræt, 2015)
It is the purpose of this article to investigate how the health-discourse looks in today’s Denmark and how the perception of bodily health has changed from the beginning of the last century until today. What is the right way to eat today and how has the diets developed into their current shape? To answer these questions a discourse analysis of health and diets seen through a historical perspective is made. Gathering and analyzing articles, adverts and diets do this from the weekly magazines, from respectively 1953, 1973, 1993 and 2013. The project is built on a social-constructivist foundation.